2023
DOI: 10.1039/d3ey00028a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in perovskite oxide electrocatalysts for Li–O2 batteries

Abstract: Lithium-oxygen batteries (LOBs) have been anticipated as promising energy-storage devices; however, their practical application is plagued by low energy efficiency, small capacity, and the short cycle life. When applied as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…Previous analysis of cobaltate and manganate perovskites have shown that local changes in bond lengths, a feature that often affects XRD patterns by broadening Bragg peaks, permits growth of such symmetry-forbidden peaks in Raman spectra by disrupting lattice symmetry. The observed changes in Raman spectra and unit cell dimensions can be understood as a replacement of Ni(III), a d 7 ion, with Co(III), a d 6 ion. This substitution contracts the c axis by removing electron density from antibonding orbitals, which is known to affect both OER and ORR according to the Sabatier principle by altering B–O bond strength. ,, The substitution also replaces an ion expected to exhibit strong Jahn–Teller expansion of B–O ax bonds with one that would prefer no expansion (Figure A), which will alter the strain distribution in the lattice. These structural changes can be confidently attributed to alteration of bonding rather than oxygen defects because oxygen stoichiometry has been shown to be insensitive to y in La 2– x Sr x Ni 1– y Co y O 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of cobaltate and manganate perovskites have shown that local changes in bond lengths, a feature that often affects XRD patterns by broadening Bragg peaks, permits growth of such symmetry-forbidden peaks in Raman spectra by disrupting lattice symmetry. The observed changes in Raman spectra and unit cell dimensions can be understood as a replacement of Ni(III), a d 7 ion, with Co(III), a d 6 ion. This substitution contracts the c axis by removing electron density from antibonding orbitals, which is known to affect both OER and ORR according to the Sabatier principle by altering B–O bond strength. ,, The substitution also replaces an ion expected to exhibit strong Jahn–Teller expansion of B–O ax bonds with one that would prefer no expansion (Figure A), which will alter the strain distribution in the lattice. These structural changes can be confidently attributed to alteration of bonding rather than oxygen defects because oxygen stoichiometry has been shown to be insensitive to y in La 2– x Sr x Ni 1– y Co y O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This substitution contracts the c axis by removing electron density from antibonding orbitals, which is known to affect both OER and ORR according to the Sabatier principle by altering B−O bond strength. 1,43,44 The substitution also replaces an ion expected to exhibit strong Jahn−Teller expansion of B−O ax bonds with one that would prefer no expansion (Figure 6A), which will alter the strain distribution in the lattice. These structural changes can be confidently attributed to alteration of bonding rather than oxygen defects because oxygen stoichiometry has been shown to be insensitive to y in La 2−x Sr x Ni 1−y Co y O 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, film‐like Li 2 O 2 tends to completely cover the cathodic surface, unfavorable to the continued growth of discharge products, resulting in poor LOBs discharge capacity. In contrast, the toroidal Li 2 O 2 possesses less contact area with the cathodic surface but larger voids, thus the corresponding LOBs exhibit larger discharge capacity but higher overpotential [72–74] . As a result, a rational design of high‐efficiency cathode catalysts is essential to control the reversible formation of discharge products.…”
Section: Fundamental Spinel‐type Electrocatalysts In Lobsmentioning
confidence: 99%
“…In contrast, the toroidal Li 2 O 2 possesses less contact area with the cathodic surface but larger voids, thus the corresponding LOBs exhibit larger discharge capacity but higher overpotential. [72][73][74] As a result, a rational design of high-efficiency cathode catalysts is essential to control the reversible formation of discharge products.…”
Section: Fundamental Spinel-type Electrocatalysts In Lobs 21 Mechanis...mentioning
confidence: 99%
“…20 The LaNiO 3 perovskite is one of the most widely investigated catalytic materials for various electrochemical applications. 23 Porous LaNiO 3 nanocubes were first employed as the cathode catalyst in a LOB in 2014. 24 With this catalyst, the charge overpotential was reduced by up to 0.35 V at 0.08 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%